Determinants of Maternal Mortality: In a Tertiary Care Hospital of Central India (International Journal of Physiology, 2020)
Introduction: Maternal mortality is unacceptably high. About 295 000 women died during and followingpregnancy and childbirth in 2017. The vast majority of these deaths (94%) occurred in low-resource settings,and most could have been prevented. Women face high risk of maternal deaths in south Asia and sub SaharanAfrica. (1)Aims and Objective: To identify causes of maternal deaths in a tertiary care hospital.Materials and Method: This is a retrospective study conducted in a tertiary level hospital of BundelkhandMedical College Sagar M.P. in central India. A retrospective case record examined related to maternalmortality in hospital setting. Ethical approval was obtained from Institutional ethical committee.Data was collected in predesigned proforma.Data were analyzed for age, gravidity, trimester of pregnancy, duration of deaths and causes of death.Results: During 1st January 2018 to 31 December 2019, 44 maternal deaths amongst 11944 live birthsoccurred in obstetrics department of Bundelkhand Medical College Sagar M.P. India.Most no. of deaths occurs in age between 21-30 years (86.4%) followed by 31-40 years (6.8%).The maternal mortality ratio (MMR) stood at 368 per lac live births. 31% were primigravida.The leading causes of death were Pre-eclampsia & Eclampsia (34%), Severe Anaemia (20%) and Hepaticencephalopathy (13%).Conclusions: Based on the results we found that hypertensive disorder (Pre-eclampsia & Eclampsia) isan important cause of maternal mortality followed by Severe Anaemia, Hepatic encephalopathy, Septicabortion and postpartum haemorrhage.Maternal mortality is a reflection of the standards of obstetric service and quality of healthcare. The auditof such mortality would help in identifying the problems and prevent recurrence by taking appropriatemeasures.Hence the present study was conducted at tertiary care hospital to review the maternal deaths and causes ofmaternal mortality